Disruption in the classroom: Experimental evidence from Ecuador - Pedro Carneiro; Yyannú Cruz Aguayo; Francesca Salvati; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2025)
We study how poorly-behaved children affect learning and other outcomes of their peers using data from a unique experiment in Ecuador. Within each school, students were randomly assigned to classrooms in every grade for seven consecutive grades, between kindergarten and 6th grade. Children with persistent behavioral problems lower the math and language achievement of their classmates. The more poorly-behaved children there are in a class, the larger is the negative effect on the achievement of their classmates. These negative impacts are larger for younger children, and they persist for at least two years after exposure to a poorly-behaved peer. We find indirect evidence that children with persistent behavioral difficulties are passed around schools.
Keywords: I24; I25; 330; Peer effects; behavioral problems